Magnetic energy fluxes in sub-Alfvénic planet star and moon planet interactions - Saur, J.; Grambusch, T.; Duling, S.; Neubauer, F. M.; Simon, S. (Astronomy and astrophysics (Berlin), 2013)
Context. Electromagnetic coupling of planetary moons with their host planets is well observed in our solar system. Similar couplings of extrasolar planets with their central stars have been studied observationally on an individual as well as on a statistical basis. Aims. We aim to model and to better understand the energetics of planet star and moon planet interactions on an individual and as well as on a statistical basis. Methods. We derived analytic expressions for the Poynting flux communicating magnetic field energy from the planetary obstacle to the central body for sub-Alfvénic interaction. We additionally present simplified, readily useable approximations for the total Poynting flux for small Alfvén Mach numbers. These energy fluxes were calculated near the obstacles and thus likely present upper limits for the fluxes arriving at the central body. We applied these expressions to satellites of our solar system and to HD 179949 b. We also performed a statistical analysis for 850 extrasolar planets. Results. Our derived Poynting fluxes compare well with the energetics and luminosities of the satellites’ footprints observed at Jupiter and Saturn. We find that 295 of 850 extrasolar planets are possibly subject to sub-Alfvénic plasma interactions with their stellar winds, but only 258 can magnetically connect to their central stars due to the orientations of the associated Alfvén wings. The total energy fluxes in the magnetic coupling of extrasolar planets vary by many orders of magnitude and can reach values larger than 1019 W. Our calculated energy fluxes generated at HD 179949 b can only explain the observed energy fluxes for exotic planetary and stellar magnetic field properties. In this case, additional energy sources triggered by the Alfvén wave energy launched at the extrasolar planet might be necessary. We provide a list of extrasolar planets where we expect planet star coupling to exhibit the largest energy fluxes. As supplementary information we also attach a table of the modeled stellar wind plasma properties and possible Poynting fluxes near all 850 extrasolar planets included in our study. Conclusions. The orders of magnitude variations in the values for the total Poynting fluxes even for close-in extrasolar planets provide a natural explanation why planet star coupling might have been only observable on an individual basis but not on a statistical basis.